2018
DOI: 10.18632/oncotarget.24429
|View full text |Cite
|
Sign up to set email alerts
|

Novel natural withanolides induce apoptosis and inhibit migration of neuroblastoma cells through down regulation of N-myc and suppression of Akt/mTOR/NF-κB activation

Abstract: Despite recent advances in intensive chemotherapy treatments, long-term success is achieved in less than 30% of children with high-risk neuroblastoma (NB). Key regulatory pathways including the PI3K/Akt, mTOR and NF-κB are implicated in the pathogenesis of NB. Although drugs targeting these individual pathways are in clinical trials, they are not effective due to the activation of compensatory mechanisms. We have previously reported that natural novel withanolides from Physalis longifolia can potently inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
(49 reference statements)
0
17
0
Order By: Relevance
“…The mTOR signaling pathway is generally known as an important regulator in cytoskeletal formation, protein synthesis, cell proliferation, growth, and apoptosis by regulating the downstream target the level of p70S6k in mammalian cells (Guo et al, 2015). Subramanian and his team found that the mTOR signaling pathway was inhibited in oxidative stress, thereby inducing apoptosis (Subramanian, Grogan, Opipari, Timmermann, & Cohen, 2018). Besides, GLUTag cells treated with H 2 O 2 had been shown that ROS production was associated with the inhibition of mTOR signaling pathways (Green, Vasu, & Flatt, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The mTOR signaling pathway is generally known as an important regulator in cytoskeletal formation, protein synthesis, cell proliferation, growth, and apoptosis by regulating the downstream target the level of p70S6k in mammalian cells (Guo et al, 2015). Subramanian and his team found that the mTOR signaling pathway was inhibited in oxidative stress, thereby inducing apoptosis (Subramanian, Grogan, Opipari, Timmermann, & Cohen, 2018). Besides, GLUTag cells treated with H 2 O 2 had been shown that ROS production was associated with the inhibition of mTOR signaling pathways (Green, Vasu, & Flatt, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Kunnimalaiyaan et al 168 has demonstrated that LY2090314 (a GSK‐3 inhibitor) is capable for causing growth inhibition and inducing apoptosis in NB cells, and also reducing the survivin level. Withanolides (WA, WGA, WGB‐DA, WGA‐TA) have also been found to be cytotoxic to NB cells, potentially because they downregulate survivin in NB cells 169 . Noscapine, a nontoxic natural compound, induces apoptosis via downregulation of survivin in both p53 wild type and null NB cells 170 .…”
Section: Preclinical Studies Of Targeted Nb Therapymentioning
confidence: 99%
“…NF-κB is a well-known target for withanolides, and its inhibition was investigated to further assess what was the role of this pathway in the antiproliferative activity observed for the withanolides included in this SAR. 41,42 Compounds that displayed an antiproliferative activity (IC 50 < 500 nM in RPMI 8226), as well as other analogues important to study SAR, were tested for their NF-κB inhibition (Table 3). Most compounds displayed a better activity than parthenolide, the positive control.…”
Section: ■ Results and Discussionmentioning
confidence: 99%